2019
DOI: 10.1111/ecc.13135
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with exercise preferences, barriers and facilitators of prostate cancer survivors

Abstract: Objective The purpose of this study was to understand the exercise levels, preferences and interests of prostate cancer survivors in Canada. Methods An electronic survey was administered via a prostate cancer‐specific website and assessed self‐reported exercise levels, exercise preferences and interests, exercise barriers and facilitators to exercise. Results Based on 103 participants, the majority (75.7%) of prostate cancer survivors did not meet both aerobic and resistance exercise guidelines, despite an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 33 publications
7
46
0
Order By: Relevance
“…The results also con rm previous qualitative work describing how men with prostate cancer who take part in a football intervention appreciate being able to share new stories from training and the value adding aspects for their husband and father operating predominately in the domestic sphere [22,25]. Moreover, the results con rm the ndings of a recent meta-synthesis of various exercise interventions and their effect on male perception of masculinity, body image, and personal identity, which concluded that exercise can facilitate a process of self-re ection secondary to changes in physique and help to re-establish male self-e cacy [26,27] .…”
Section: Discussionsupporting
confidence: 77%
“…The results also con rm previous qualitative work describing how men with prostate cancer who take part in a football intervention appreciate being able to share new stories from training and the value adding aspects for their husband and father operating predominately in the domestic sphere [22,25]. Moreover, the results con rm the ndings of a recent meta-synthesis of various exercise interventions and their effect on male perception of masculinity, body image, and personal identity, which concluded that exercise can facilitate a process of self-re ection secondary to changes in physique and help to re-establish male self-e cacy [26,27] .…”
Section: Discussionsupporting
confidence: 77%
“…25 Despite strong evidence supporting the safety and efficacy of exercise in individuals with prostate cancer, evaluations of this population show that the majority of prostate cancer survivors are insufficiently active. 28,29,37,38,[76][77][78] The reported proportion of individuals with prostate cancer who meet the aerobic and resistance exercise guidelines varies based on the method used to evaluate exercise levels (objective or self-reported). 28,33,37,[76][77][78] The majority of studies report only on aerobic exercise levels and generally find that individuals with prostate cancer are performing insufficient amounts of moderate-to-vigorous aerobic exercise or physical activity (depending on measurement and definition).…”
Section: Ability Of Individuals With Prostate Cancer To Meet Exercisementioning
confidence: 99%
“…28,29,37,38,[76][77][78] The reported proportion of individuals with prostate cancer who meet the aerobic and resistance exercise guidelines varies based on the method used to evaluate exercise levels (objective or self-reported). 28,33,37,[76][77][78] The majority of studies report only on aerobic exercise levels and generally find that individuals with prostate cancer are performing insufficient amounts of moderate-to-vigorous aerobic exercise or physical activity (depending on measurement and definition). 33,37,77 One of the larger studies in prostate cancer is a crosssectional study by Chipperfield et al (2013) that evaluated the aerobic exercise levels of 365…”
Section: Ability Of Individuals With Prostate Cancer To Meet Exercisementioning
confidence: 99%
See 2 more Smart Citations